FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA TRANSAKSI BERJALAN INDONESIA - Handoko, Rudi (Badan kebijakan Fiskal, 2010)
This paper attempt to describe factors affecting the performance of current account in Indonesia. Current account performance is showed by surplus or deficit position. Analysis of the factors is conducted based on periodization of current account performance. Other analysis was carried out by using scatter graph to show the relationship between two variables in question. The results show that some factors affecting current account performance are global economic growth, Indonesian major trading partners growth, domestic economic growth, international commodities prices, exchange rate management, economic policy, and financial crisis.